Brazilian medicinal plants - Modolo, Luzia V. (Boca Raton, Florida : CRC Press, 2019)
"The vast and exciting Brazilian flora biodiversity is still underexplored. Several research groups are devoted to the study of the chemical structure richness found in the different Biomes. This volume presents a comprehensive account of the research collated on natural products produced from Brazilian medicinal plants and focuses on various aspects of the field. The authors describe the key natural products and their extracts with emphasis upon sources, an appreciation of these complex molecules and applications in science. Many of the extracts are today associated with important drugs, nutrition products, beverages, perfumes, cosmetics and pigments,and these are highlighted"--
OCLC-licensed vendor bibliographic record.
Keywords: Medicinal plants -- Brazil; Medicinal plants -- Brazil -- Identification; SCIENCE / Chemistry / General; SCIENCE / Life Sciences / Botany